Broomcorn Stalk Fiber in Nonwoven Reinforced Polylactic Acid Matrix Composites - Ahmet Özgür Ağırgan (BioResources)
The broomcorn plant (Sorghum bicolor (L.) Moench) is one of the main cereal crops and its grains are used in food and feed sectors while its stems are used in broom production and as a building material. Polylactic acid (PLA) is a biobased polymer that is widely used as a matrix material in natural fiber-reinforced composites. In this study, the aim is to use broomcorn plant stems, which are agricultural waste, as reinforcement in composite production. For this purpose, fiber was obtained by purifying broomcorn plant stems from woody cells with enzyme and NaOH. To easily comb the fibers, 10 wt% cotton was added and blended and turned into nonwoven fabric via needle punching. Then, PLA was combined with the matrix using the hot press method to produce single and double-layered composites. To characterize the broomcorn fiber reinforced composite material, strength, elongation, scanning electron microscopy, and Fourier transform infrared instrumental methods were used within the standards. According to the analysis results, broomcorn fiber has a high potential as a new reinforcement material suitable for composite production.